Local residents’ willingness to donate for low carbon city initiatives in Taiping, Perak: proposed e-bike-sharing project - Poon, Chi Yong; Matthew, Nitanan Koshy; Ponrahono, Zakiah; Sahrir, Syazwani; Ya'cob, Mohd Rusli (Malaysian Institute Of Planners, 2024)
The transport sector in Malaysia ranked second in the country's total energy consumption for 2021, thereby contributing to greenhouse gas emissions. Numerous cities strive to attain low-carbon urban environments. E-bikes, as environmentally friendly vehicles, have the potential to play a significant role in urban transportation by contributing to the creation of low-carbon cities. Taiping, Perak, has been recognised as one of the world's top 3 most sustainable cities for 2019. This prestigious accolade positions it as an ideal location for an e-bike project, further solidifying its commitment to maintaining its status as a sustainable city. This study seeks to evaluate the awareness and attitudes of Taiping residents towards e-bikes, determine the factors that influence their willingness to donate, and ascertain the average amount they are willing to contribute to the e-bike-sharing development project in Taiping, Perak. A survey was conducted with 385 respondents using the Contingent Valuation Method, employing stratified random sampling. The findings indicated a notable level of awareness and favourable attitudes towards e-bikes. Factors such as bid, age, education, income, and awareness impact the willingness to donate. On average, each person contributes RM10.40 towards the proposed e-bike-sharing project in Taiping. The discovery offered valuable insights to the Taiping Municipal Council regarding securing financial support and better understanding residents' perspectives on e-bike sharing.